Spindle Cell Lipoma of the Dorsal Parts of the Foot - Muzaffer Durmuş; Abdül Kerim Yapıcı; İbrahim Yavan; Fatih Zor; Serdar Öztürk (Turkish Journal of Plastic Surgery, 2016)
Spindle cell lipoma (SCL) is a tumor of the mature fat tissue that the collagen producing spindle cells take place in varying proportions. Most frequently, it settles on the back and neck and is located in the subcutaneous tissue. It is commonly seen in male patients in the 4th–5th decades. In addition to immunohistochemical examination, histopathological examination is necessary for the differential diagnosis. In this study, a spindle cell lipoma located on the dorsal foot was discussed along with the current literature review.